2020
DOI: 10.1074/jbc.ra120.013926
|View full text |Cite
|
Sign up to set email alerts
|

Blood group P1 antigen–bearing glycoproteins are functional but less efficient receptors of Shiga toxin than conventional glycolipid-based receptors

Abstract: Shiga toxin (STx) is a virulence factor produced by enterohemorrhagic Escherichia coli. STx is taken up by mammalian host cells by binding to the glycosphingolipid (GSL) globotriaosylceramide (Gb3; Galα1-4Galβ1-4Glc-ceramide) and causes cell death after its retrograde membrane transport. However, the contribution of the hydrophobic portion of Gb3 (ceramide) to STx transport remains unclear. In pigeons, blood group P1 glycan antigens (Galα1-4Galβ1-4GlcNAc-) are expressed on gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…The released N -glycans were derivatized with PA as described previously 48 . Mixtures of PA- N -glycans were separated by HPLC using a TSKgel DEAE-5PW column as described previously 39 , 49 . PA-glycans were detected using an FLD with an excitation wavelength of 310 nm and an emission wavelength of 380 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The released N -glycans were derivatized with PA as described previously 48 . Mixtures of PA- N -glycans were separated by HPLC using a TSKgel DEAE-5PW column as described previously 39 , 49 . PA-glycans were detected using an FLD with an excitation wavelength of 310 nm and an emission wavelength of 380 nm.…”
Section: Methodsmentioning
confidence: 99%
“…A recently published article showed that glycoproteins carrying the P1 glycotope synthesized by the pigeon homolog of human Gb3/CD77 synthase may serve as functional receptors for Stx1 ( 69 ). The authors knocked out the genes encoding glucosylceramide and galactosylceramide synthases in HeLa cells, and used these cells to overexpress a pigeon homolog of human Gb3/CD77 synthase.…”
Section: Discussionmentioning
confidence: 99%
“…The unmodified HeLa cells produce Gb3, but not P1 glycoproteins. Interestingly, when Morimoto et al expressed the pigeon homolog of human Gb3/CD77 synthase in unmodified HeLa and obtained cells producing both Gb3 and P1 glycoproteins, these were less sensitive to Stx1 than unmodified cells (69). The authors suggest that P1 glycoproteins served as decoy receptors for the toxin, but it should be noted that HeLa cells expressing the pigeon homolog produced less Gb3 than unmodified cells, so it could be that the P1 glycoproteins were not able to compensate for the loss of Gb3, the GSL being a more potent receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, birds belonging to the Neoaves parvclass (but not to Galloanserae parvclass and Paleognathae infraclass) express Galα1→4Gal on glycoproteins, including egg white glycoproteins [ 15 ]. In a recently published article, Morimoto et al [ 16 ] reported two different genes encoding the Gb3/CD77 synthase homologs in the wild pigeon ( Columba livia ). They proposed that one of them, named A4GALT 1, encodes an enzyme that synthesizes GSLs but not glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme encoded by the other gene, called A4GALT 2, was analyzed in detail and it showed dual activity; its main acceptors are glycoproteins, but it can also synthesize Gb3, although at a lower rate. In addition, the authors showed that glycoproteins with terminal Galα1→4Gal may act as functional receptors for Shiga toxins, although much less effective than glycosphingolipids [ 16 ].…”
Section: Introductionmentioning
confidence: 99%